2004
DOI: 10.1161/01.res.0000119322.87051.a9
|View full text |Cite
|
Sign up to set email alerts
|

Restitution of Action Potential Duration During Sequential Changes in Diastolic Intervals Shows Multimodal Behavior

Abstract: Abstract-Restitution of action potential duration (APD) is thought to be critical in activation instability. Although restitution is used to predict APD during sequential changes in diastolic interval (DI), currently used protocols to determine restitution do not use sequential changes in DI. We explored restitution using a new pacing protocol to change DI sequentially and independently of APD. Transmembrane potentials were recorded from right ventricular endocardial tissue isolated from six dogs. We used thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 34 publications
1
65
0
Order By: Relevance
“…This long string of constant cycle lengths removes any effects of short-term cardiac memory associated with variations in cycle length such as occur during VF. 18 Cardiac memory is the phenomenon in which not just the previous DI but also the previous APD, as well as the DIs and APDs of even earlier cycles, influence APD. 19,20 In addition to restitution, cardiac memory may also be important during VF.…”
mentioning
confidence: 99%
“…This long string of constant cycle lengths removes any effects of short-term cardiac memory associated with variations in cycle length such as occur during VF. 18 Cardiac memory is the phenomenon in which not just the previous DI but also the previous APD, as well as the DIs and APDs of even earlier cycles, influence APD. 19,20 In addition to restitution, cardiac memory may also be important during VF.…”
mentioning
confidence: 99%
“…6 -9 The APD observed at any given DI is not unique and depends on the history of activation sequence leading up to that beat. In this issue of Circulation Research, Wu and Patwardhan 10 report on APD restitution in canine isolated ventricular tissue preparations using oscillatory sequences of DI. These investigators made use of a system they previously developed 11 to provide explicit control over DI by starting a timer when the action potential achieved 90% repolarization and stimulating the tissue when the elapsed time reached the prescribed DI for that beat.…”
mentioning
confidence: 99%
“…Wu and Patwardhan 10 found that the relationship between APD and preceding DI followed a hysteresis loop rather than a fixed unimodal curve when DI varied sinusoidally. For a given DI, APD was consistently lower when DI was on the rising limb than when DI was falling.…”
mentioning
confidence: 99%
“…It is likely that the increase in APD after a short DI (Figure 3) is a result of accumulation of memory due to longer APDs during preceding activations. 16 In a previous porcine study, 5 memory together with restitution showed only 30% contribution to APD variability. That study used a microelectrode on the epicardium of an openchest intubated-ventilated porcine model, and the ␣ level for retention of a variable in the model was 0.25.…”
Section: Short-term Memory During Vfmentioning
confidence: 83%
“…14 Short-term memory is the concept in which APD is determined not only by previous DI but also by APDs from earlier cycles. 15,16 Short-term memory may contribute to APD variance during VF in which the cycle length is not constant. To test these hypotheses, we studied the relative contribution of APD restitution relationship and short-term memory effects on APD variation during early VF in myopathic hearts using the monophasic action potential (MAP) catheter in patients.…”
Section: Clinical Perspective On P 570mentioning
confidence: 99%